Establishing causal relationships between sleep and adiposity traits using Mendelian randomization. Issue 3 (15th February 2023) - Hayes, Bryony L.; Vabistsevits, Marina; Martin, Richard M.; Lawlor, Deborah A.; Richmond, Rebecca C.; Robinson, Timothy
Abstract: Objective: The aim of this study was to systematically evaluate the direction of any potential causal effect between sleep and adiposity traits. Methods: Two‐sample Mendelian randomization was used to assess the association of genetically predicted sleep traits with adiposity and vice versa. Using data from UK Biobank and 23andMe, the sleep traits explored were morning preference (chronotype; N  = 697, 828), insomnia ( N  = 1, 331, 010), sleep duration ( N  = 446, 118), napping ( N  = 452, 633), and daytime sleepiness ( N  = 452, 071). Using data from the Genetic Investigation of ANthropometric Traits (GIANT) and Early Growth Genetics (EGG) consortia, the adiposity traits explored were adult BMI, hip circumference (HC), waist circumference (WC), waist‐hip ratio (WHR; N  = 322, 154), and childhood BMI ( N  = 35, 668). Results: This study found evidence that insomnia symptoms increased mean WC, BMI, and WHR (difference in means, WC = 0.39 SD [95% CI: 0.13‐0.64], BMI = 0.47 SD [95% CI: 0.22‐0.73], and WHR = 0.34 SD [95% CI: 0.16‐0.52]). Napping increased mean WHR (0.23 SD [95% CI: 0.08‐0.39]). Higher HC, WC, and adult BMI increased odds of daytime sleepiness (HC = 0.02 SD [95% CI: 0.01‐0.04], WC = 0.04 SD [95% CI: 0.01‐0.06], and BMI 0.02 SD [95% CI: 0.00‐0.04]). This study also found that higher mean childhood BMI resulted in lower odds of napping (−0.01 SD [95% CI: 0.02‐0.00]). Conclusions: The effects of insomnia on adiposity and of adiposity on daytime sleepiness suggest that poor sleep and weight gain may contribute to a feedback loop that could be detrimental to overall health.